Isomerization of Cis-2-Butene to Trans-2-Butene in a Plug Flow Reactor: A Simulation Study Using Aspen HYSYS V14 - Rudy Agustriyanto; Endang Srihari Mochni; Edy Purwanto; Puguh Setyopratomo (Direktorat Penerbitan dan Publikasi Ilmiah, Universitas Surabaya, 2024)
Abstract—This study investigates the isomerization of cis-2-butene to trans-2-butene in a single-tube Plug Flow Reactor (PFR) using Aspen HYSYS V14 for process simulation. The reaction is modeled as a homogeneous, irreversible isomerization with first-order kinetics (rate constant k=0.003833 s−1). The objective was to determine the optimal reactor volume and channel diameter to achieve 95% conversion of cis-2-butene under specified conditions: 1 meter reactor length, 100 kgmol/h feed rate, 12 bar pressure, and 25°C. The Peng-Robinson fluid package was employed for thermodynamic calculations. Simulation results indicate that a reactor volume of 2.268 m³ and channel diameter of 1.699 m are required to achieve the target conversion. This study demonstrates the efficacy of Aspen HYSYS in reactor design optimization and provides valuable insights for industrial applications of butene isomerization. The methodology presented offers a robust framework for addressing similar chemical engineering challenges. Keywords: aspen HYSYS, butene, isomerization, plug flow reactor, process simulation. Abstrak—Penelitian ini menyelidiki isomerisasi cis-2-butena menjadi trans-2-butena dalam Reaktor Aliran Sumbat (PFR) tabung tunggal dengan menggunakan Aspen HYSYS V14 untuk simulasi proses. Reaksi dimodelkan sebagai isomerisasi homogen irreversible, dengan kinetika orde pertama (konstanta kecepatan reaksi k = 0,003833 s−1). Tujuan penelitian ini adalah menentukan volume reaktor dan diameter saluran yang optimal untuk mencapai konversi cis-2-butena sebesar 95% di bawah kondisi yang telah ditentukan: panjang reaktor 1 meter, laju umpan 100 kgmol/jam, tekanan 12 bar, dan suhu 25°C. Paket fluida Peng-Robinson digunakan untuk perhitungan termodinamika. Hasil simulasi menunjukkan bahwa volume reaktor sebesar 2,268 m³ dan diameter saluran sebesar 1,699 m diperlukan untuk mencapai konversi yang ditargetkan. Penelitian ini menunjukkan efektivitas Aspen HYSYS dalam optimasi desain reaktor dan memberikan wawasan berharga untuk aplikasi industri isomerisasi butena. Metodologi yang dipresentasikan menawarkan kerangka kerja yang kuat untuk mengatasi tantangan rekayasa kimia serupa. Kata kunci: aspen HYSYS, butena, isomerisasi, plug flow reaktor, simulasi proses